Urban forms interpretation for the car-era spaces reuse. A comparison of walking, automobile, and sustainable cities - Guaiani, Alessia (TeMA - Journal of Land Use, Mobility and Environment, 2024)
The shape of the city is described in various ways, but it’s not incorrect to view it as the result of intricate connections between tangible components and intangible influences, specifically the behaviors of its inhabitants. Over the last century, through the Modern Movement and the impulses of the CIAM, the studies of typological, technological, and stylistic innovation necessary to give the character of ‘rationality’ to the shape construction, summarized in the metaphor of ‘machinist civilization’, have produced infrastructures and urban spaces dedicated to the automobile efficiency. Today, the issue of sustainability is bursting into all sectors, shaping new urban and mobility models, mainly based on non-motorized travel. A situation not too different from that which has characterized cities in the past, in particular Italian realities. Starting from these conditions and from the identification of a strong link between urban structure and mobility, the paper gives an interpretation of Italian cases able to connect the different components of the city, made up of spatial dimensions, represented by the urban structure, and temporal dimensions, identified in mobility patterns. Beginning with the walking city model, which is 30-minute walkable, the historic city, the rationalist one of the automobile city, and the polycentric structures are investigated to trace examples of design that can still be valid today and understand the possibilities to reuse the automobile-age spaces.